Assessment of jaw muscles and cervical spine muscles isometric force using a hand-held dynamometer in young adults - Onofrei, Roxana Ramona; Amaricai, Elena (Balneo and PRM Research Journal (Online. English ed.), 2023)
Our study aims to investigate the jaw and cervical spine muscle isometric forces in healthy young adults. Fifty-four subjects (21.2 ± 4.82 years) met the inclusion criteria and agreed to par-ticipate in the study. Muscle forces were assessed with a hand-held dynamometer. A significant positive correlation was found between jaw opening forces and cervical flexors forces (r=0.62, p0.0001) and between lateral mandible deviation forces and cervical spine lateral flexion forces, both for right and left side (r=0.65, p<0.0001; r=0.69, p<0.0001, respectively. In healthy young adults, using a hand-held dynamometer for muscle strength testing, significant positive correla-tion was found between jaw opening forces and cervical flexors forces and between lateral mo-uth deviation force and cervical spine lateral flexion forces, both for right and left side. The rela-tionship between jaw muscles forces and cervical spine muscles forces is a topic that needs to be further studied, also together with posture and balance.